Possible uses of infrared thermography in sport - Korman, Paweł; Zieliński, Jacek; Kusy Krzysztof; Straburzyńska-Lupa, Anna (Akademia Wychowania Fizycznego w Poznaniu)
The authors discuss the physiological bases of thermographic research and review its current applications in sport performance diagnostics on the basis of available professional literature. The methodology of thermographic studies involves the proper preparation of the workstation, thermographic equipment, and the athlete. The authors also refer to the results of their own research conducted during real training sessions. Factors influencing the obtained outcomes are discussed.
Keywords: sport performance; thermography; influence factors; skin temperature